1998
DOI: 10.1097/00005537-199812000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of endonasal endoscopic dacryocystorhinostomy and external dacryocystorhinostomy

Abstract: EXT-DCR, when compared with EESC-DCR, appears to give a higher, although not statistically significant, primary success rate, but the secondary success rates are equal, indicating that these two different DCR techniques are acceptable alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
187
2
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(218 citation statements)
references
References 13 publications
13
187
2
12
Order By: Relevance
“…The success rate for EES-DCR, however, varies markedly from 54 to 96%. [1][2][3][4][5][6][7][8] Numerous modifications have been developed to promote ostial patency, ranging from various methods of producing the nasal mucosal and/or lacrimal sac flaps, 2,4,[9][10][11][12] varying the size of the bony ostium, 4,[12][13][14] lacrimal sac incision, 15 to stenting. 16,17 Nevertheless, ostial closure or obstruction still occurs, mostly due to excessive scars/synechia or granulation formation at the ostium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success rate for EES-DCR, however, varies markedly from 54 to 96%. [1][2][3][4][5][6][7][8] Numerous modifications have been developed to promote ostial patency, ranging from various methods of producing the nasal mucosal and/or lacrimal sac flaps, 2,4,[9][10][11][12] varying the size of the bony ostium, 4,[12][13][14] lacrimal sac incision, 15 to stenting. 16,17 Nevertheless, ostial closure or obstruction still occurs, mostly due to excessive scars/synechia or granulation formation at the ostium.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Nevertheless, ostial closure or obstruction still occurs, mostly due to excessive scars/synechia or granulation formation at the ostium. 3,5,6,8,9,[18][19][20] Some authors advocate the use of mitomycin C (MMC) intraoperatively to reduce fibrosis formation, [21][22][23][24][25][26] although granulation tissue has been reported to form around the ostia following MMC application during EES-DCR. 27,28 Hyaluronan is a ubiquitous polysaccharide component of the extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Wormald et al 11 , Sham et al 12 and Hartikainen et al 2 used drills to cause saccular exposure and ensure that through these instruments there is exposure of the more reliable lacrimal sac, which is ensured by the use of the chisel. Using the endonasal technique with chisel and hammer, and the use of power-driven drills, we did not observe any significant difference between these two approaches (p≤ 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Hartikainem et al 2 compared these two techniques in 64 cases and found success rates in 75% for DCR EN and 91% for DCR EX. These poor results may be explained by the fact that these patients have been submitted to small rhinostomies, with 7mm diameter, emphasizing the importance of a wide window between the sac and the nasal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…A dacriocistorrinostomia por via externa foi usada com sucesso no tratamento da epífora com sistema lacrimal pérvio e obstruções incompletas (3) . Para obstrução lacrimal completa, comparando-se a via externa com a via endoscópica, os resultados descritos na literatura tem sido um pouco melhores pela via externa (10) . O'Donnel refere excelentes resultados (94%) com a DCR por via externa para epífora com sistema lacrimal patente (5) .…”
Section: Discussionunclassified